2015
DOI: 10.1007/s40520-015-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive function is necessary for the regulation of the stepping activity when stepping in place in older adults

Abstract: To determine the effect of age on stepping performance and to compare the cognitive demand required to regulate repetitive stepping between older and younger adults while performing a stepping in place task (SIP). Fourteen younger (25.4 ± 6.5) and 15 older adults (71.0 ± 9.0) participated in this study. They performed a seated category fluency task and Stroop test, followed by a 60 s SIP task. Following this, both the cognitive and motor tasks were performed simultaneously. We assessed cognitive performance, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
11
1
2
Order By: Relevance
“…Our study indicated a significant relationship between PA and executive function. Higher-level executive function was reported to be necessary for the regulation of PA in a cohort study [ 32 ]. Improvements in executive function correlated with increases in gait speed and PA in a prospective cohort study of community-dwelling older adults with falls [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study indicated a significant relationship between PA and executive function. Higher-level executive function was reported to be necessary for the regulation of PA in a cohort study [ 32 ]. Improvements in executive function correlated with increases in gait speed and PA in a prospective cohort study of community-dwelling older adults with falls [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several long-term trials have shown that PA is associated with executive function [ 15 , 28 ]. The PAs that showed effects towards executive function are as follows: aerobic walking [ 29 ], dual task-based exercise training [ 30 ], two sessions of exercise training [ 31 ], stepping activity [ 32 ], crossing a street at a pedestrian traffic light [ 33 ], and social participation [ 17 ]. Conversely, the PAs that did not show any positive effects on executive function include stretching and balance exercises [ 34 ], slow jogging [ 35 ], resistance exercise [ 36 ], moderate-intensity walking exercise [ 37 ], flexibility training [ 38 ], and single-task training [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Walking is a cognitive process which requires higher-level control and is not an automatic movement ( LeMonda et al, 2015 ). Studies have demonstrated that executive functions, attention and memory are closely related to walking ( Dalton, Sciadas & Nantel, 2015 ). Executive functions refer to a variety of higher cognitive processes that modulate and use information from the posterior cortical sensory systems to produce behavior ( Honan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, several other studies have shown that motor control of daily motor tasks (gait, balance, etc.) depends, at least in part, on executive functions [46][47][48][49]. Accordingly, since executive functions are strongly altered in older adults, motor control is impaired, which is manifested by impairments in balance or locomotory tasks [50][51].…”
Section: The Relevance Of Physical-cognitive Dual-task Trainingmentioning
confidence: 99%